Desenvolvimento humano e reintegração social: reflexões sobre a educação em prisões na Paraíba - Silva Júnior, Edvaldo Ferreira da (2022)
The general objective of this research was to analyse education offered in prisons in the state of Paraiba as part of a public policy for the social reintegration of people deprived of their liberty and its capacity to produce concrete effects with relation to the prison population which it should serve. The person who is deprived of his liberty has the right to access, in the prison itself, public policies of education, whose educational processes, as important representations of State actions which promote, in principle, the social reintegration of men and women prisoners. As a material representation of the very right to education, these educational processes are highlighted as tools for the development of these diverse individuals and, consequently, possess a relevant connexion with the social reintegration of the imprisoned person. However, despite its centrality, the debate concerning its effectivity is relevant to avoid the return to the system of criminal justice of people who, in some way, even with limitations on their freedom of movement, returned to social conviviality. To that end, this study verified by means of bibliographic research, the production of primary data during fieldwork research and documental analysis anchored in statistical studies and documents collected from different institutions, how education in prisons in Paraiba, with regard to its sufficiency and the possibility of producing concrete effects, impacts the social reintegration of imprisoned persons. Thus, initially, a bibliographic survey demonstrated that educational processes in prisons, given the instrumental character of education, when developed in isolation and without connecting it with other actions directed to health, nutrition, work, income, training, professionalization, etc. and for want of a dignified environment with regard to its material conditions and social interactions, as public policy, are not sufficient for the social reintegration of people deprived of their liberty. And more, based on objective facts and primary elements, it also became clear that in Paraiba, when faced by the current infrastructure and its scope in relation to the prison population which it should serve, education in prisons in the state of Paraiba cannot be considered effective, as a possibility for producing concrete effects, for avoiding the return to the system of criminal justice of ex-prisoners from that same system.